Fenomenología y Humanismo en Eugenio Pucciarelli - Breuer, Irene (Ekstasis: Revista de Hermenêutica e Fenomenologia, 2021)
The article deals with the Argentine philosopher Eugenio Pucciarelli’s critical reception of phenomenology and his conception of humanism. After introducing Pucciarelli and his main contribution to philosophy and in particular, to phenomenology in Latin America, the article deals with his conceptions of the following issues: first, the mission of philosophy and the diverse ways of access into the essence of philosophy, in particular those of Scheler, Dilthey and Husserl; second, the Husserlian phenomenology as it concerns the ideal of science and reason; third, Pucciarelli’s denouncing the crisis of reason and evidence; fourth, the pluralism of images of reason and time. The article concludes with an exposition of Pucciarelli’s own humanistic stance. I claim that his ideal of humanism, which emphasizes the personal dimension and social commitment of doing philosophy, reveals a profound pluralistic humanism that does not neglect its militant and critical function, ensuring thus the actuality of Pucciarelli’s message.